Optimization of machining parameters in turning of LM6 high silicon aluminium alloy using aluminium titanium nitride and diamond like carbon coated carbide tool. (2021) - Kamatchi Hariharan, M.; Anderson, A.; Ravi Kumar, K.; Senthilkumar, A.
Abstract: Aluminium alloys are well known for its wide applications in automobile and aviation field. In 4000 series aluminium alloy, silicon has been used as alloying element ranging from 4% to 13% in composition. Turning of high silicon materials, will results in more amount of friction and increase in thermal stresses between the machining tools and workpieces. In this work, LM6 aluminium alloy (High silicon aluminium alloy) has been taken as work material and turning process with both uncoated and AlTiN& DLC (Aluminium Titanium Nitride and Diamond like carbon) coated carbide inserts, in both dry and wet environments have been performed. To study the tribological behaviour, cutting speed, feed rate and depth of cut have been preferred as machining variables and average surface roughness for all machining conditions has been measured. All the machining parameters have been taken with 3 levels and machining process is carried out with full factorial approach. All the responses have been recorded in the Minitab statistical software for finding the optimized values for machining the high silicon aluminium alloy. The most proficient outcome of the experiments conducted is found to be under machining in wet environment with coated carbide tool resulted in 0.1562 μm.